Development of Energy-Efficient Biomass Stove for Meretrix Casta Processing by Community Participation of Palian River Basin Community, Trang Province - Wunsri, Supranee; Podkumnerd, Noppadon; Somalee, Chompunooch; Teeparuksapun, Kosin (Area Based Development Research Journal, 2020)
This research aims to develop an energy saving biomass stove for Meretrix casta processing of Palian river basin, Trang province. The participatory action research (PAR) was performed with Ban Laem Meretrix casta processing group, Kantang district, Trang province. Research procedures included data collection, development of a biomass stove prototype, investigation of biomass stove and knowledge dissemination to Palian river basin community. The research showed that the technology could reduce boiling time of Meretrix casta from 268 to 195 minutes with the temperature in front of the stove of only 32 ºC. This could reduce 65% of fuel consumption when compared to the homemade stove. In addition, the clam meat boiled on developed biomass stove was denser than that on homemade stove. The technology transfer to the community resulted in higher potential in production of Meretrix casta processing, from 800 to 1,600 kg/month. The income increased from 8,000 to 16,000 Baht per month. The total increased income from April 2019 to March 2020 was 192,000 Baht. In conclusion, the project also made use of material waste from cigarette wrapping production as alternative fuel to replace para wood, leading to 30 % of fuel cost; thus, enabling the technology transferred to Ban Na Hin Rad and Ban Tha-rue communities.